Prognostic Utility of the Combination of Platelet Count with Neutrophil-to-Lymphocyte Ratio in Aged Patients with Acute Myocardial Infarction Undergoing Percutaneous Coronary Intervention - Xiao-Qing Quan; Hong-Yan Ji; Jie Jiang; Jia-Bao Huang; Cun-Tai Zhang (Emergency Medicine International)
Background and Aim. Acute myocardial infarction represents the vital cause of cardiac death, and many measurable biomarkers have been reported to be related to the prognosis of acute myocardial infarction. Our study was to investigate the role of a novel biomarker, the combination of platelet count, and neutrophil-to-lymphocyte ratio, for predicting in-hospital and long-term mortality of aged patients with acute myocardial infarction. Method. This was a study recording 637 patients who were diagnosed with acute myocardial infarction. Our patients were grouped according to the combination of platelet count and neutrophil-to-lymphocyte ratio. The prognostic role of the combination of platelet count and neutrophil-to-lymphocyte ratio on mortality was assessed by the univariate and multivariate Cox regression analysis. Result. Our study population was divided into three parts according to the median values of platelet count and neutrophil-to-lymphocyte ratio. It was indicated that platelet count and neutrophil-to-lymphocyte ratio were correlative mutually to a certain degree (p=0.010). The Kaplan–Meier analysis showed that the combination of high platelet count and high neutrophil-to-lymphocyte ratio had a greater risk of death in short- and long-term endpoints (log-rank p=0.046, p<0.001, respectively). Moreover, by multivariate analysis, both high platelet count and high neutrophil-to-lymphocyte ratio groups were an independent predictor (hazard ratio: 2.132, 95% confidence interval: 1.020–4.454, p=0.044) and long-term mortality (hazard ratio: 2.791, 95% confidence interval: 1.406–5.538, p=0.003). Conclusion. The combination of platelet count and neutrophil-to-lymphocyte ratio could be a useful predictor for the prediction of in-hospital and long-term mortality in aged patients with acute myocardial infarction.